2013
DOI: 10.1021/cm4006844
|View full text |Cite
|
Sign up to set email alerts
|

Optimized Synthesis of CdTe Nanoplatelets and Photoresponse of CdTe Nanoplatelets Films

Abstract: We study in details the synthesis of CdTe nanoplatelets. Three populations of nanoplatelets with a thickness defined with atomic precision are obtained. We show that CdTe nanoplatelets can be extended laterally to obtain nanosheets with lateral dimensions in the micron range. We present the study of the reaction conditions for the formation of CdTe nanoplatelets and for their lateral extensions. The reaction products are analyzed with optical spectroscopy, transmission electron microscopy and small angle X-ray… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
181
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 108 publications
(196 citation statements)
references
References 46 publications
15
181
0
Order By: Relevance
“…However, we failed to prepare 5 ML thick CdTe NPLs by following the protocol described in ref. 31. Nevertheless, we were able to synthesize 4 ML normal CdSe (core)-CdTe(wings) and inverted CdTe (core)-CdSe-(wings) hetero-NPLs ( Fig.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…However, we failed to prepare 5 ML thick CdTe NPLs by following the protocol described in ref. 31. Nevertheless, we were able to synthesize 4 ML normal CdSe (core)-CdTe(wings) and inverted CdTe (core)-CdSe-(wings) hetero-NPLs ( Fig.…”
Section: Resultsmentioning
confidence: 98%
“…At the same time semiconductor NCs with 1D quantum confinement (quantum nanoplatelets, NPLs) composed of cadmium chalcogenides are currently being extensively studied [28][29][30][31][32] and expected to be promising materials for the preparation of semiconductor HNCs with efficient charge separation. Such NPLs exhibit electronic and optical properties that differ from those for QDs, such as much narrower absorption and PL bands (FWHM < 10 nm), a giant oscillator strength, lower thresholds for amplified spontaneous emission and higher optical gain saturation.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, an absorption feature appearing within the spectral region of 550−560 nm emerges and becomes comparable to the electron/light-hole and electron/heavy-hole transitions of CdSe NPLs as the CdTe crown is grown larger. This red-shifted sharp absorption peak (∼556 nm) thus corresponds to the formation of excitons in the 4 ML thick CdTe crown layer, 35 and the intensity of this peak can be tuned by changing the size of the CdTe crown layer. Also, it was shown that higher concentration of OA results in formation of extended CdTe crown region and enhances the absorption of crown region.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…140,142 CdS nanoplates come with a large lateral extension. Compared to CdSe, their optical absorption is broader.…”
Section: Figure 21: Tem Images Of Cdse Npls With Small (A) and Large mentioning
confidence: 99%